Biomonitoring of Pollution by Microalgae Community in Aquatic System with Special Reference to Water Quality of River Kolong, Nagaon, Assam, India - Buragohain, Bharat Banti; Yasmin, Farishta (International Journal of Applied Sciences and Biotechnology, 2014)
<!–[if gte mso 9]> 800x600 <![endif]–> With growing urbanization and industrialization India faces the challenge of providing clean and safe drinking water. In the name of economic growth most rivers and streams are turning into sewers. Pollution effect is equally damaging both biotic and abiotic components. Microalgae play an interesting role in forecasting changing environment. Pollution in aquatic environment like changing pH; addition of oil, heavy metals; increase of organic matter and chemical fertilizers can be traced by studying algal community. Abundant growth of particular algae, drastic change in species diversity and depletion of long inhabitant algal flora indicates the pollution in a very initial stage. In the present study, attempt has been made to point out some indicator algae of Kolong River which is getting polluted day by day and in placed among the 71 most polluted stretch of river in the country. In our investigation, we have found microalgae mainly from groups Chlorophyceae, Cyanophyceae and Desmidiaceae which can be identified as indicator species in biomonitoring purpose. DOI: http://dx.doi.org/10.3126/ijasbt.v2i1.9345 Int J Appl Sci Biotechnol, Vol 2(1): 45-49 <!–[if gte mso 9]> Normal 0 false false false EN-IN X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Calibri","sans-serif"; –> <!–[endif] –>